PENGARUH STRUKTUR MODAL DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN YANG DIMEDIASI KINERJA KEUANGAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL PEMODERASI PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA TAHUN 2011-2014 - Dinda Yulmi Nadillah; Yulia Efni; Andewi Rokhmawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this research is to exemine the effect of Capital Structure, Growth Opportunites to Firm Value in which Financial Performance as intervening variabel Corporate Social Responsibility as moderating variable. Endogenous variables in this research are Firm Value and Financial Performance. Futhermore the exogenous variables are Capital Structur and Growth Oppornites. Population of this research was 142 manufacturing firms listed in Indonesia Stock Exchange periode of 2011-2014. The sample of this research was 80 firms that selected based on purposive sampling techniques. To process the data, this research runs regression analysis with path analysis by utilizing SPSS software version 20. The results showed that Financial Performance and Capital Structure have a positive and significant effect on Firm Value. Growth Opportunities has a negative and not significant effect on the Firm Value. Financial Performance was able to intervene the effect of Capital Structure and Growth Opportunities on the Firm Value. Finally, Corporate Social Responsibility (CSR) strengthens the influence of Financial Performance on the firm value.Keyword : Capital Structure (SM), Growth Opportinities (PP), Financial Performance (KK), Firm Value (NP) and Corporate Social Responsibility (CSR)